Profiling Student Learning Styles to Design Differentiated Learning to Support Independent Learning - Ichsan Fahrozi; Putri Yanuarita Sutikno (Universitas Pendidikan Ganesha, 2024)
Another obstacle teachers often face is the lack of learning facilities that can support the implementation of the independent curriculum. Based on this, this research aims to produce significant data or information related to the profiling characteristics of student learning styles, especially the learning styles of fifth-grade elementary school students, which can be used to optimise learning activities through differentiated learning. This type of research is qualitative research. This research uses the case study method to explore reality, implementing different learning through profiling student learning styles. The research subjects were the principal, teachers and class V students. The methods used to collect data were interviews, observation and student questionnaires. The data analysis technique used in this research is descriptive qualitative with the Miles and Huberman version of the data analysis technique. The research results show that class V students have their dominant learning styles. Teachers use this as a basis for designing differentiated learning that is adapted to the characteristics of students' learning styles. The fifth-grade teacher also implemented several learning strategies to overcome difficulties and shortcomings in implementing differentiated learning.